2004
DOI: 10.1111/j.1365-3040.2004.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

New evidence for a role of vessel‐associated cells and phloem in the rapid xylem refilling of cavitated stems of Laurus nobilis L.

Abstract: Xylem recovery from embolism was studied in Laurus nobilis L. stems that were induced to cavitate by combining negative xylem pressure potentials ( P X = = = = ----1.1 MPa) with positive air pressures ( P C ) applied using a pressure collar. Xylem refilling was measured by recording the percentage loss of hydraulic conductance (PLC) with respect to the maximum 2 min, 20 min and 15 h after pressure release. Sodium orthovanadate (an inhibitor of many ATP-ases) strongly inhibited xylem refilling while fusicoccin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
234
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(256 citation statements)
references
References 57 publications
8
234
1
4
Order By: Relevance
“…Salleo et al, 2004;Salleo et al, 2006). A theoretical study by Hölttä et al (2006b) showed that water released by sugar unloading from the phloem may induce xylem embolism refilling in certain conditions.…”
Section: Solute Relaysmentioning
confidence: 99%
“…Salleo et al, 2004;Salleo et al, 2006). A theoretical study by Hölttä et al (2006b) showed that water released by sugar unloading from the phloem may induce xylem embolism refilling in certain conditions.…”
Section: Solute Relaysmentioning
confidence: 99%
“…Boyer (1989) argued that drying of the soil may result in the collapse of the water potential gradient between xylem and actively-dividing cells. When roots were severed, Salleo et al (2000Salleo et al ( , 2004 showed that plants closed their stomata to reduce the occurrence of cavitation and to prevent the decrease in Ψ L . The apparent recovery in Ψ L after root severing observed here (Fig.…”
Section: Nature Of the Root Signalmentioning
confidence: 99%
“…This common, even daily, event (2-4) can lead to complete failure of the hydraulic system if runaway embolism occurs (5). Two of the three attributes by which plants' negative-pressure flow systems can be protected against failure, resistance and reparability, have been subjects of active research during the last decade (2)(3)(4)(6)(7)(8)(9)(10). The third attribute, redundancy, has received much less attention as an important drought adaptation but is emerging as a focus of research (11)(12)(13)(14).…”
mentioning
confidence: 99%